Phylogenetic and morphological characterization of Komarekiella atlantica (Cyanobacteria, Nostocales) from southernmost subtropical Brazilian environments - Vanessa Maria Didoné; Luis Henrique Zanini Branco; Mariéllen Dornelles Martins; Vera Regina Werner (Brazilian Journal of Microbiology, 2026)

Co-parasitism by chigger mites (Trombidiformes: Leeuwenhoekiidae) and soft ticks (Ixodida: Argasidae) in Brazilian anurans, with the description of a new Hannemania species - Isabella Pereira Pesenato; Ricardo Bassini-Silva; Pedro Paulo Goulart Taucci; Nadya Carolina Pupin; Murillo Castelo Branco Monho; Giovanna Rafaeli Rezende; Maria Eduarda Barbosa de Souza-Silva; Sebastian Muñoz-Leal; Marcelo B. Labruna; Darci Moraes Barros-Battesti; Fernando de Castro Jacinavicius (Systematic Parasitology, 2026)
Bokermannohyla frogs comprise species distributed across different Brazilian biomes, several of which are currently listed as endangered species. These anurans host a diversity of parasites that may negatively affect their survival. Several tick species of the family Argasidae and chigger mites of the family Leeuwenhoekiidae exhibit host specificity toward this group. Here, we report a case of co-parasitism by argasid ticks and chigger mites in this frog genus collected in the Bahia State, Brazil, and describe a new species of Hannemania, H. diamantinensis sp. nov. Anurans were captured in Chapada Diamantina National Park, and ectoparasites were collected and identified using morphological methods. Ticks were identified as Ornithodoros saraivai , while chigger mites correspond to a new species. This represents the first record of O. saraivai in Bahia State, and the description of a new Hannemania species increases the number of Brazilian known species to eight.

Functional landscape connectivity and cropland context influence spider abundance in the ecological infrastructure of Mediterranean agricultural floodplains - Saskia Doherty; João Pedro Nunes; Paulo Branco; Vera Zina; André Fonseca; José Carlos Franco; Manuela Branco; Pedro Segurado; Maria Teresa Ferreira; Gonçalo Duarte (Agriculture, Ecosystems & Environment, 2026)

Geraniol disrupts mature MRSA biofilms on venous catheters and shows synergistic activity with oxacillin against planktonic cells - Lisandra Juvêncio da Silva; Vitória Pessoa de Farias Cabral; Lara Elloyse Almeida Moreira; Daniel Sampaio Rodrigues; Leilson Carvalho de Oliveira; Maria Janielly Castelo Branco Silveira; Elaine Aires de Lima; Dávylla Rênnia Saldanha Pinheiro; Sarah Alves Barbosa; Cecília Rocha da Silva; Lívia Gurgel do Amaral Valente Sá; João Batista de Andrade Neto; et al. (Biofouling, 2026)

From invasive nuisance to biotechnological asset: LC–MS/MS chemical profiling and pharmacological potential of ascidian Styela plicata from Albufeira Lagoon, Portugal - Maria João Nunes; Catarina M. Luís; Vanda Marques; Bárbara Gonçalves; Luís C. Branco; Cecília M. P. Rodrigues; Rita G. Sobral; Susana P. Gaudêncio (Environmental Science and Pollution Research, 2026)

Enabling policy coherence in a polycentric system: The MonitoraEA platform as an informational meta-governance infrastructure in Brazil - Evandro Albiach Branco; Ricardo Zylbergeld; Ana Maria Amorim; Celly Kelly Neivas dos Santos; Maria Henriqueta Andrade Raymundo; Rachel Andriollo Trovarelli; Marcos Sorrentino (Environmental Science & Policy, 2026)

Morphological characterization of the buccopharyngeal region in tadpoles of Physalaemus ephippifer (Steindachner, 1864), Anura, Leptodactylidae - Ailin C. Branco; Fabrielle B. Araújo; Adrian J. O. Reis; Brenda S. Braga; Maria Luiza C. Souza-Ferreira; Verônica R. L. Oliveira-Bahia (Zoomorphology, 2026)
Studies on the microanatomy of the tadpole oral apparatus are limited, particularly for Amazonian species. Therefore, the present study aimed to describe the ontogenetic development, as well as the buccopharyngeal morphology, of the oral apparatus of Physalaemus ephippifer tadpoles. Egg clutches were transported to the laboratory and maintained in plastic containers filled with water at an average temperature of 24 °C, where embryonic and larval development took place. Periodic sampling was conducted according to developmental stage, and specimens were analyzed using light and scanning electron microscopy. At stage 18, the stomodeum was formed. By stage 21, thickening of the lower and posterior lips was observed, together with the development of the upper and lower horny beaks. At stage 23, five lips with denticles became apparent. By stage 25, the oral apparatus was fully developed, exhibiting a dental formula of 2(2)/3(1). The internal cavity contained several papillae, and both the dorsal and ventral velum were observed at the posterior end of the buccopharyngeal cavity. The development of the oral apparatus in P. ephippifer follows a pattern similar to that observed in other Physalaemus species; however, the main difference lies in the timing of structural development. This study contributes to a better understanding of the taxonomic identification and feeding behavior of this species and provides additional knowledge about the regional amphibian fauna.

Temperature rise modulates the competitive interaction between Microcystis aeruginosa (Cyanobacteria) and Gymnodinium sp. (Dinophyceae): Insights into the bloom dynamics of two co-occurring species - Vanessa Guarino Pereira; Suema Branco; Lúcia Helena Sampaio da Silva; Sandra Maria Feliciano de Oliveira e Azevedo; Mauro Cesar Palmeira Vilar (Journal of Applied Phycology, 2026)
Climatic events driven by rising global temperature impact water quality and biota, in some cases leading to cyanobacterial blooms. Cyanobacteria and dinoflagellates can dominate phytoplankton communities, forming mixed or alternating harmful blooms whose shifts are influenced by seasonal temperature fluctuations. Microcystis aeruginosa , a microcystin-producing cyanobacterium, has formed dense blooms worldwide. Under certain conditions, M. aeruginosa alternates dominance with dinoflagellates, a phenomenon reported in several lakes. This study tested the hypotheses that increasing temperature would allow i) M. aeruginosa to outcompete Gymnodinium sp. and ii) stimulate production of temporary cysts by the dinoflagellate as a stress response. Batch cultures were established using mono- and co-cultures at 23 °C (control) and 30 °C (high temperature) for 14 days. Growth, photosynthetic activity, microcystin concentration, and cyst production were measured. The temperature increase alone did not influence the growth or photosynthetic performance of either species. However, in co-culture at 23 °C, M . aeruginosa showed enhanced growth and photosynthetic performance, whereas at 30 °C it exhibited lower microcystin concentration. For Gymnodinium sp., the combination of elevated temperature and interaction with M. aeruginosa had a negative impact, reducing growth, lowering photosynthetic efficiency, and increasing cyst formation. Under elevated temperature, M. aeruginosa gained a competitive advantage over the dinoflagellate. This, in turn, increased cyst formation as a stress response and survival strategy, favoring Microcystis through competition over resource exploitation rather than through direct physiological effects. These findings reinforce that warming may shift the phytoplankton structure toward cyanobacterial dominance, posing challenges for water quality and ecosystem management.

Laterality in Neotropical psittacids (Aves, Psittacidae): Evaluation of its relationships with temperament and social interactions - Larissa Gomes; Gustavo Nunes de Almeida; Maria Eduarda Caçador Branco; Aline Cristina Sant’Anna (Applied Animal Behaviour Science, 2026)

A bibliometric review about scientific trends and advances on residual feed intake (RFI) and feed efficiency in ruminants - Josiel Ferreira; Lucas Ferreira Gonçalves; Tiago do Prado Paim; Sarah Figueiredo Martins Bonilha; Joslaine Noely dos Santos Goncalves Cyrillo; Maria Eugênia Zerlotti Mercadante; Renata Helena Branco Arnandes; Ricardo Lopes Dias da Costa; Concepta McManus (Tropical Animal Health and Production, 2026)
The increasing demand for sustainable livestock production systems has intensified scientific interest in feed efficiency traits, particularly residual feed intake (RFI), as a strategy to improve productivity while reducing environmental impacts. This study provides a comprehensive bibliometric assessment of global scientific production on RFI and feed efficiency in ruminants. A total of 2632 documents indexed in Scopus and Web of Science databases between 2015 and 2024 were analyzed, covering 374 scientific sources and involving 8,406 authors. Scientific output showed a strong and consistent upward trend throughout the study period, with an annual growth rate of 48.9%, particularly from 2019 onwards. Brazil, United States, Australia, Canada, and China were identified as the leading contributors to research development in this field. Authorship patterns revealed a highly collaborative research structure, with an average of 6.97 co-authors per publication, reflecting the interdisciplinary nature of feed efficiency studies. Keyword co-occurrence and network analyses highlighted the close integration of RFI research with themes related to sustainability, methane emissions, genetics, nutrition, and rumen biology. Overall, the results indicate that research on RFI has evolved from a predominantly zootechnical indicator toward a consolidated and sustainability-oriented scientific domain, reinforcing its strategic importance for the development of climate-smart ruminant production systems.

Role of autonomic receptors in ethyl ferulate-induced cardiovascular effects in normotensive and hypertensive female rats - Francisca Valdirene de S. Nunes; Samuel S. P. Araujo; Juliana A. da Silva; José Guilherme V. de Assunção; Ariell A. de Oliveira; Carlos E. R. Dourado; Vandercley de O. Damasceno; Aldeídia P. de Oliveira; Maria do Carmo C. Martins; Mayara C. de Morais; Damião P. de Sousa; Thyago M. de Queiroz; et al. (Pflügers Archiv - European Journal of Physiology, 2026)
Aims Ethyl ferulate (EF) may offer novel benefits in hypertension. We investigated the contribution of autonomic receptors to EF-induced effects in female Wistar and SHR. Methods Anesthetized females received EF intravenously at 7.5, 15, or 30 mg/kg. Autonomic involvement was evaluated using pretreatment with atropine, atenolol, or hexamethonium. MAP and HR were continuously monitored. Results EF induced rapid and pronounced reductions in MAP and HR in both strains. In Wistar rats, muscarinic and nicotinic blockade significantly attenuated these responses. In SHR, atropine abolished bradycardia and partially mitigated hypotension, whereas β1-adrenergic and nitric oxide synthase inhibition had minimal impact. Conclusion EF acutely lowers MAP and HR, with muscarinic and nicotinic receptors driving the effects in normotensive females, and muscarinic pathways partially mediating responses in hypertensive females. These results position EF as a compelling candidate for antihypertensive therapy and underscore the critical need to study cardiovascular interventions in female hypertension models.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Moving towards Europe-wide freshwater restoration through model-based integration of policy objectives - Andrea Funk; Gonçalo Duarte; Paulo Branco; Thomas Hein; Astrid Schmidt-Kloiber; Tamara Leite; Angeliki Peponi; Maria Teresa Ferreira; Sebastian Birk; Annette Baattrup-Pedersen; Florian Borgwardt (Water Research, 2026)

Can Green Scenarios Improve Water Ecosystem Services and Mitigate the Effects of Climate Change? A Case Study in a River Basin in Southeastern Brazil - Phelipe da Silva Anjinho; Angeliki Peponi; Gonçalo Duarte; Paulo Branco; Maria Teresa Ferreira; Frederico Fabio Mauad (Environmental Management, 2026)

Preventive activity of promethazine against fluconazole-resistant Candida spp. biofilms fixed on urinary catheters - Cecília Rocha da Silva; João Batista de Andrade Neto; Vitória Pessoa de Farias Cabral; Érica Rayanne Mota da Costa; Daniel Sampaio Rodrigues; Lara Elloyse Almeida Moreira; Thais Lima Ferreira; Maria Janielly Castelo Branco Silveira; Elaine Aires de Lima; Ana Carolina Medeiros de Oliveira; Wildson Max Barbosa da Silva; Manoel Odorico de Moraes; et al. (Biofouling, 2026)

Diet of White-Cheeked Spider Monkeys (Ateles marginatus) in Continuous Forests at the Cristalino Private Reserve (Mato Grosso – Brazil) - Paola Cardias Soares; Gustavo Rodrigues Canale; Maria Aparecida Lopes; Makupa Kayabi; Bruno Castelo Branco Damiani; Leandro Pereira Piva; Liza Maria Veiga (International Journal of Primatology, 2026)

Reflection about articaine: in vitro studies and clinical data - RE: Schwann cells exposed to articaine display distinct toxic pathways compared to lidocaine by Rodrigues da Silva et al. - Chem Biol Interact. 2025 Jan 25; 406: 111315 - Filipe Polese Branco; Maria Cristina Leme Godoy dos Santos (Chemico-Biological Interactions, 2026)

Dexamethasone modulates cytokine and chemokine secretion by CD4 + T cells from SSc patients and exerts antifibrotic effects in HOCl-induced SSc mice - Maria Eduarda de Oliveira Gonçalves; Anderson Rodrigues de Almeida; Andréa Tavares Dantas; Karen Steffani Silva Florencio; Júlia Roberta da Silva Ferreira; Felipe Henrique dos Santos Barbosa; Ryan Cordeiro Silva; Anderson Arnaldo da Silva; Daniel Neri da Matta; Angela Luzia Branco Pinto Duarte; Moacyr Jesus Barreto de Melo Rêgo; Michelly Cristiny Pereira; et al. (Inflammopharmacology, 2026)

Wound healing and anti-inflammatory effects of LAA, the N-acetyl-d-galactosamine-binding lectin from seeds of Luetzelburgia auriculata (Allemão) ducke - Karla Lilian Rodrigues Batista; Lucas dos Santos Silva; Izadora Souza Soeiro Silva; Miria Yasmim Miranda Paiva; João Lucas Sales Santos; Carlos Eduardo Morais de Sousa; Simeone Júlio dos Santos Castelo Branco; Felipe Eduardo Alves de Paiva; Renato Rodrigues Roma; Fábio Souza Ananias Oliveira; Patrícia Maria Guedes Paiva; Cléver Gomes Cardoso; et al. (Histochemistry and Cell Biology, 2025)

Cratylia mollis lectin reduces inflammatory burden induced by multidrug-resistant Staphylococcus aureus in diabetic wounds - Lucas dos Santos Silva; Simeone Júlio dos Santos Castelo Branco; Izadora Souza Soeiro Silva; Miria Yasmim Miranda Paiva; Beatriz Gomes Vila Nova; Carlos Emanuel de Matos Chaves Lima; Weslley Felix de Oliveira; Felipe Eduardo Alves de Paiva; Patrícia Maria Guedes Paiva; Andrea de Souza Monteiro; Claudener Souza Teixeira; Cléver Gomes Cardoso; et al. (Histochemistry and Cell Biology, 2025)

Optimized conditions for broth microdilution susceptibility testing of Trichosporon spp. to clinical antifungals - Isabela Lima Miranda; Nalu Teixeira Aguiar Peres; Rafael Wesley Bastos; Luana Rossato; Gabriela Silva Cruz; Maria Isabel Azevedo; Kássia Jéssica Galdino Silva; Débora S. C. M. Castelo-Branco; Fabíola Lucini; Daniel Assis Santos (Brazilian Journal of Microbiology, 2025)

Antibacterial and antibiofilm activity of ruthenium polypyridine complex against Staphylococcus strains - Leonardo Silva de Sousa; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Felipe Diógenes Abreu; Eduardo Henrique Silva Sousa; Idalina Maria Moreira de Carvalho; Débora S. C. M. Castelo-Branco; Mayron Alves de Vasconcelos; Edson Holanda Teixeira (Biofouling, 2025)

Pilot-scale application of selected microbial starters to enhance the nutritional and sensorial traits of fermented and pasteurized table olives - Annamaria Tarantini; Anna Rita Bavaro; Leonardo Mancini; Angelica Bruno; Giuseppe Celano; Chiara Medoro; Marta Cianciabella; Isabella D'Antuono; Giuseppe Romano; Leone D'Amico; Pierpaolo Branco; Stefano Predieri; et al. (International Journal of Food Microbiology, 2025)

Chemical profile of extracts from wild and farmed Chondrosia reniformis sponges - Maria João Nunes; Despoina Varamogianni-Mamatsi; Vanda Marques; Thekla I. Anastasiou; Eirini Kagiampaki; Emmanouela Vernadou; Thanos Dailianis; Nicolas Kalogerakis; Luís C. Branco; Cecília M. P. Rodrigues; Rita G. Sobral; Manolis Mandalakis; et al. (Aquaculture International, 2025)

Enhanced antimicrobial and antibiofilm activities of ruthenium complexes with fluorine- and bromine-substituted ligands against staphylococcal strains - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Isa Maria Ferreira Azevedo; Tatiane Gomes da Silva; Paula Victoria Soares; Ellen Araújo Malveira; José Marcos da Silveira Carvalho; Débora S. C. M. Castelo-Branco; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2025)

Antibacterial potential of antidepressants against extended-spectrum β-lactamase-producing Escherichia coli - Cecília Rocha da Silva; Lívia Gurgel do Amaral Valente Sá; Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Lara Elloyse Almeida Moreira; Érica Rayanne Mota da Costa; Thais Lima Ferreira; Maria Janielly Castelo Branco Silveira; Tatiana do Nascimento Paiva Coutinho; Letícia Bernardo Barbosa; Igor Gomes Aguiar; Bruno Coêlho Cavalcanti; et al. (Folia Microbiologica, 2025)

Correction: Tetramethylpyrazine alleviates hepatic fibrosis induced by experimental mansonic schistosomiasis - Ana Carolina Campos dos Santos; Daniel Figueiredo-Vanzan; Josiane Bentes; Juliana Maria Motta; Hilton Antônio Mata-Santos; Alexandre dos Santos Pyrrho; Morgana Teixeira Lima Castelo-Branco (Inflammopharmacology, 2025)

Translational insights into statin-induced myotoxicity: Differential impact of lipophilic and hydrophilic statins on iPSC-derived skeletal muscle cells from patients with familial hypercholesterolemia - Raul Hernandes Bortolin; Felipe de Souza Leite; Andre Ducati Luchessi; Joyce Esposito; Igor Neves Barbosa; Renata Caroline Costa de Freitas; Abhijeet Rajendra Sonawane; Sasha Anna Singh; Elena Aikawa; Kayque Alves Telles-Silva; Thiago Dominguez Crespo Hirata; Antonia Pereira Rosa Neta; et al. (Toxicology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Evaluation of the quality of bovine semen subjected to cryopreservation with hydroxypropylmethylcellulose - Anna Monallysa Silva de Oliveira; Nívia Maria Rocha Brandão; Anailson De Oliveira Maciel; Nágylla Santos De Almeida; Nayonara Santos De Almeida; Thiago Santos Santos; Izakiel Reis Marinho; Francisco Cardoso Figueiredo; Yndyra Nayan Teixeira Carvalho Castelo Branco; José Adalmir Torres de Souza (Reproductive Biology, 2025)

Ultrastructure and androgen analysis during sex inversion of Brycon orbignyanus reared in captivity - Patricia Postingel Quirino; Maria Luiza Ribeiro Delgado; Luciane Gomes-Silva; Giovana Souza Branco; Renata Guimarães Moreira; Alexandre Ninhaus-Silveira; Rosicleire Veríssimo-Silveira (Fish Physiology and Biochemistry, 2025)

EHMT2 as a Candidate Gene for an Autosomal Recessive Neurodevelopmental Syndrome - Laura Machado Lara Carvalho; Jessica Rzasa; Jennifer Kerkhof; Haley McConkey; Veniamin Fishman; Galina Koksharova; Alexander Augusto de Lima Jorge; Elisa Varella Branco; Danyllo Felipe de Oliveira; Beatriz Martinez-Delgado; Maria J. Barrero; Tjitske Kleefstra; et al. (Molecular Neurobiology, 2025)

Tetramethylpyrazine alleviates hepatic fibrosis induced by experimental mansonic schistosomiasis - Ana Carolina Campos dos Santos; Daniel Figueiredo-Vanzan; Josiane Bentes; Juliana Maria Motta; Hilton Antônio Mata-Santos; Alexandre dos Santos Pyrrho; Morgana Teixeira Lima Castelo-Branco (Inflammopharmacology, 2025)

Inhibition of calcineurin as a strategy for biofilm control: Trichosporon spp. as a case study - Bruno Nascimento da Silva; Ana Raquel Colares de Andrade; Francisco Eilton Sousa Lopes; Ana Luiza Ribeiro Aguiar; Fernando Victor Monteiro Portela; Maria Laina Silva; Brendda Miranda Vasconcelos; José Júlio Costa Sidrim; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2025)

Effect of promethazine against Staphylococcus aureus and its preventive action in the formation of biofilms on silicone catheters - Érica Rayanne Mota da Costa; Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Thais Lima Ferreira; Maria Janielly Castelo Branco Silveira; Leilson Carvalho de Oliveira; Lívia Gurgel do Amaral Valente Sá; Cecília Rocha da Silva; João Batista de Andrade Neto; Sorele Facundo da Silva; Bruno Coêlho Cavalcanti; Manoel Odorico de Moraes; et al. (Biofouling, 2025)

Antifungal resistance in yeasts from One Health perspective: A Brazilian study - Rafael Wesley Bastos; Nalu Teixeira de Aguiar Peres; Kássia Jéssica Galdino da Silva; Ludmila Gouveia Eufrasio; Daniel Santana de Carvalho; Gabriela Silva Cruz; Fabíola Lucini; Lorena Souza Silva; Sthefany Emanuelle Silva; Hareton Teixeira Vechi; Manoella do Monte Alves; Luciana Rodrigues Ferreira Ribeiro; et al. (Science of The Total Environment, 2025)

Effects of climate on leaf phenolics, insect herbivory, and their relationship in pedunculate oak (Quercus robur) across its geographic range in Europe - Elena Valdés-Correcher; Yasmine Kadiri; Audrey Bourdin; Anna Mrazova; Flavius Bălăcenoiu; Manuela Branco; Michal Bogdziewicz; Mona Chor Bjørn; Thomas Damestoy; Jovan Dobrosavljević; Maria Faticov; Sofia Gripenberg; et al. (Oecologia, 2025)
An increase in biotic interactions towards lower latitudes is one of the most consistent patterns in ecology. Higher temperatures and more stable climatic conditions at low latitudes are thought to enhance biotic interactions, accelerating biological evolution and leading to stronger anti-herbivore defences in plants. However, some studies report contradictory findings, highlighting the need for further investigation into the underlying mechanisms. We used a combination of field observations and feeding trials in controlled environments to investigate the effect of climate on chemical defences and insect herbivory in pedunculate oak ( Quercus robur L.) throughout most of its geographic range in Europe, while controlling for physical defences. The concentration of lignin, flavonoids, and total phenolics increased significantly with temperature, whereas both field herbivory and weight of spongy moth ( Lymantria dispar L.) larvae were negatively influenced by temperature. Lignin concentration positively influenced the weight of spongy moth larvae whereas it had no effect on field herbivory. We found no evidence of strong positive relationships between insect herbivory and larvae growth with leaf defences. Our study underscores the complexity of plant–herbivore interactions along climatic gradients and highlights the need for further research to disentangle these intricate relationships.

Genomic and epidemiological surveillance of SARS-CoV-2 variants during the pre-mass vaccination period in Botucatu, Brazil - Felipe Allan da Silva da Costa; Patricia Akemi Assato; Karen Ingrid Tasca; Leonardo Nazário de Moraes; Drielle Baptista dos Santos Figueiredo; Gabriela Ribeiro; Alex Ranieri Jerônimo Lima; Sandra Coccuzzo Sampaio; Maria Carolina Quartim Barbosa Elias Sabbaga; Carlos Magno Castelo Branco Fortaleza; Jayme Augusto de Souza-Neto; Rejane Maria Tommasini Grotto (Virus Genes, 2025)

Collaborative approaches to urban tree biosecurity: Stakeholder’s perceptions, actions and social networks - Alessandro Paletto; Carlotta Sergiacomi; Mariella Marzano; Mersudin Avdibegović; Marta Bełka; Kathrin Blumenstein; Helena Bragança; Manuela R. Branco; Daiva Burokienė; Julio Javier Diez Casero; Ilija D. Đorđević; Zuzana Dobšinská; et al. (Urban Forestry & Urban Greening, 2025)

Establishment and Molecular Validation of a Lima Bean (Phaseolus lunatus) Core Collection in Brazil - Rafael da Costa Almeida; Leonardo Castelo Branco Carvalho; Alessandro Alves-Pereira; Josilane Souza da Penha; Verônica Brito da Silva; Maria Imaculada Zucchi; José Baldin Pinheiro; Jaime Martínez-Castillo; Ângela Celis de Almeida Lopes; Regina Lucia Ferreira Gomes (Plant Molecular Biology Reporter, 2025)

Antifungal susceptibility, clinical findings, and biofilm resistance of Fusarium species causing keratitis: a challenge for disease control - Pedro de Freitas Santos Manzi de Souza; Edlâny Pinho Romão Milanez; Ana Raquel Colares de Andrade; Lua Silva; Maria Laína Silva; Ruan Costa Monteiro; Anderson Messias Rodrigues; Débora Castelo Branco de Souza Collares Maia; Glaucia Morgana de Melo Guedes; Rossana de Aguiar Cordeiro (Brazilian Journal of Microbiology, 2025)

Ontogeny of adenohypophyseal cells, pituitary gland development, and structure in adults of Astyanax lacustris (Teleostei, Characiformes): an emerging Neotropical model fish species - Giovana Souza Branco; Monica Cassel; Chayrra Chehade; Marília de Paiva Camargo; Gisele Cristiane de Melo Dias; Maria Ines Borella; Lázaro Wender Oliveira de Jesus (Fish Physiology and Biochemistry, 2025)

Fermentation-mediated sustainable development and improvement of quality of plant-based foods: from waste to a new food - Elisabete Hiromi Hashimoto; Aline de Cassia Campos Pena; Mário Antônio Alves da Cunha; Ricardo de Freitas Branco; Kely Priscila de Lima; Gustavo Henrique Couto; Maria Giovana Binder Pagnoncelli (Systems Microbiology and Biomanufacturing, 2025)

Antifungal activity of tannic acid against Candida spp. and its mechanism of action - Lara Elloyse Almeida Moreira; Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Amanda Dias Barbosa; Maria Janielly Castelo Branco Silveira; Tatiana do Nascimento Paiva Coutinho; Sarah Alves Barbosa; Lívia Gurgel do Amaral Valente Sá; João Batista de Andrade Neto; Sania Nara Costa da Rocha; Celina Santos Reis; Bruno Coelho Cavalcanti; et al. (Brazilian Journal of Microbiology, 2024)

A review of relevant parameters for assessing indoor air quality in educational facilities - Pedro T.B.S. Branco; Sofia I.V. Sousa; Marzenna R. Dudzińska; Duygu Gazioglu Ruzgar; Mustafa Mutlu; Georgios Panaras; Giannis Papadopoulos; John Saffell; Ana Maria Scutaru; Christian Struck; Annemarie Weersink (Environmental Research, 2024)

The European Union-Mercosur Free Trade Agreement as a tool for environmentally sustainable land use governance - Susan E.M. Cesar de Oliveira; Jaqueline C. Visentin; Bruna F. Pavani; Paulo D. Branco; Marcello de Maria; Rafael Loyola (Environmental Science & Policy, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Antibiotics stimulates the development of persistent cells in biofilms of Candida albicans bloodstream isolates - Fernando Victor Monteiro Portela; Ana Raquel Colares de Andrade; Lívia Maria Galdino Pereira; Bruno Nascimento da Silva; Paulo Henrique Soares Peixoto; Bruno Rocha Amando; Nicole de Mello Fiallos; Pedro de Freitas Santos Manzi de Souza; Reginaldo Gonçalves de Lima-Neto; Glaucia Morgana de Melo Guedes; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2024)

Study of the effects of pasteurization and selected microbial starters on functional traits of fermented table olives - Annamaria Tarantini; Pasquale Crupi; Francesca Anna Ramires; Leone D'Amico; Giuseppe Romano; Federica Blando; Pierpaolo Branco; Maria Lisa Clodoveo; Filomena Corbo; Angela Cardinali; Gianluca Bleve (Food Microbiology, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Temperament of Psittaciformes: A systematic review - Gustavo Nunes de Almeida; Gabriela Ramos; Larissa Gomes de Jesus; Maria Eduarda Caçador Branco; Cristiano Schetini de Azevedo; Aline Cristina Sant’Anna (Applied Animal Behaviour Science, 2024)

Cosmetic degradation: A study on body lotions with botanical extracts - Andreia Branco; Cristina Soares; Cristina Delerue-Matos; Maria João Ramalhosa; Valentina F. Domingues (South African Journal of Botany, 2024)

Chitosan hydrochloride-gum Arabic-passion fruit seed oil nanoparticle edible coating to control fungal infection and maintain quality parameters of strawberries - Alessandra Silva Araújo; Gerlane Souza de Lima; Ihasmyn dos Santos Nunes; Júlio César Ribeiro de Oliveira Farias de Aguiar; Daniela Maria do Amaral Ferraz Navarro; Natália Ferrão Castelo Branco Melo; Nereide Stela Santos Magalhães; Rodrigo França; Rafaela de Siqueira Ferraz Carvalho; Thayza Christina Montenegro Stamford (Food Control, 2024)

Eugenia uniflora (pitanga) juice as a new alternative vehicle for Limosilactobacillus fermentum ATCC 23271: evaluation of antioxidant and anti-infective effects - Gabrielle Damasceno Costa dos Santos; Carlos Drielson da Silva Pereira; Camila Caetano da Silva; Marcos Andrade Silva; Lucas dos Santos Silva; Brenda da Silva Cutrim; Simeone Júlio dos Santos Castelo Branco; Patrícia Maria Guedes Paiva; Maria Tereza dos Santos Correia; Rita de Cássia Mendonça de Miranda; Adrielle Zagmignan; Luís Cláudio Nascimento da Silva (Brazilian Journal of Microbiology, 2024)

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

PPARγ partial agonist LPSF/GQ-16 prevents dermal and pulmonary fibrosis in HOCl-induced systemic sclerosis (SSc) and modulates cytokine production in PBMC of SSc patients - Anderson Rodrigues de Almeida; Andréa Tavares Dantas; Maria Eduarda de Oliveira Gonçalves; Charlotte Chêne; Mohamed Jeljeli; Sandrine Chouzenoux; Marine Thomas; Eudes Gustavo Constantino Cunha; Lilian David de Azevedo Valadares; João Victor de Melo Gomes; Simão Kalebe Silva de Paula; Marina Galdino da Rocha Pitta; et al. (Inflammopharmacology, 2024)

A two-pronged approach against glioblastoma: drug repurposing and nanoformulation design for in situ-controlled release - Maria Mendes; Francisco Branco; Rui Vitorino; João Sousa; Alberto Pais; Carla Vitorino (Drug Delivery and Translational Research, 2023)
Glioblastoma (GB) is one of the most lethal types of neoplasms. Its biologically aggressive nature and the presence of the blood–brain barrier (BBB) limit the efficacy of standard therapies. Several strategies are currently being developed to both overcome the BBB and deliver drugs site specifically to tumor cells. This work hypothesizes a two-pronged approach to tackle GB: drug repurposing with celecoxib (CXB) and a nanoformulation using ultra-small nanostructured lipid carriers (usNLCs). CXB antitumor druggable activity was inspected bioinformatically and screened in four glioma cell lines aiming at the comparison with temozolomide (TMZ), as standard of care. Delving into formulation design, it was tailored aiming at (i) improving the drug solubility/loading properties, (ii) assigning a thermal-triggerable drug release based on a lipid matrix with a low melting point, and (iii) enhancing the cytotoxic effect by selecting a template targetable to tumor cells. For this purpose, an integrated analysis of the critical material attributes (CMAs), critical process parameters (CPPs), and critical quality attributes (CQAs) was conducted under the umbrella of a quality by design approach. CMAs that demonstrate a high-risk level for the final quality and performance of the usNLCs include the drug solubility in lipids (solid and liquid), the lipid composition (envisioning a thermoresponsive approach), the ratio between lipids (solid vs. liquid), and the surfactant type and concentration. Particle size was shown to be governed by the interaction lipid-surfactant followed by surfactant type. The drug encapsulation did not influence colloidal characteristics, making it a promising carrier for lipophilic drugs. In general, usNLCs exhibited a controlled drug release during the 72 h at 37 °C with a final release of ca. 25%, while at 45 °C this was doubled. The in vitro cellular performance depended on the surfactant type and lipid composition, with the formulations containing a sole solid lipid (Suppocire ® NB) and Kolliphor ® RH40 as surfactant being the most cytotoxic. usNLCs with an average diameter of ca. 70 nm and a narrow size distribution (PdI lower than 0.2) were yielded, exhibiting high stability, drug protection, sustained and thermo-sensitive release properties, and high cytotoxicity to glioma cells, meeting the suitable CQAs for parenteral administration. This formulation may pave the way to a multi-addressable purpose to improve GB treatment. Graphical Abstract

Polyhexamethylene guanidine hydrochloride as promising active ingredient for oral antiseptic products to eliminate microorganisms threatening the health of endangered wild cats: a comparative study with chlorhexidine digluconate - Renata Alves de Barros; Marcela Aldrovani Rodrigues; Sérgio Ricardo Ambrósio; Rodrigo Cássio SolaVeneziani; Daniel Paulino Júnior; Renato Luis Tame Parreira; Maria Anita Lemos Vasconcelos Ambrósio; Thayná de Souza Silva; Lucas de Freitas Pereira; Messias Gonçalves Pessinato; Vinícius José da Silva Cardoso de Brito; César Henrique Branco; et al. (Brazilian Journal of Microbiology, 2023)

Measuring healthy ageing: current and future tools - Nádia Silva; Ana Teresa Rajado; Filipa Esteves; David Brito; Joana Apolónio; Vânia Palma Roberto; Alexandra Binnie; Inês Araújo; Clévio Nóbrega; José Bragança; Pedro Castelo-Branco; Raquel P. Andrade; et al. (Biogerontology, 2023)
Human ageing is a complex, multifactorial process characterised by physiological damage, increased risk of age-related diseases and inevitable functional deterioration. As the population of the world grows older, placing significant strain on social and healthcare resources, there is a growing need to identify reliable and easy-to-employ markers of healthy ageing for early detection of ageing trajectories and disease risk. Such markers would allow for the targeted implementation of strategies or treatments that can lessen suffering, disability, and dependence in old age. In this review, we summarise the healthy ageing scores reported in the literature, with a focus on the past 5 years, and compare and contrast the variables employed. The use of approaches to determine biological age, molecular biomarkers, ageing trajectories, and multi-omics ageing scores are reviewed. We conclude that the ideal healthy ageing score is multisystemic and able to encompass all of the potential alterations associated with ageing. It should also be longitudinal and able to accurately predict ageing complications at an early stage in order to maximize the chances of successful early intervention.

Swimming under Pressure: The Sub-Lethal Effects of a Pesticide on the Behaviour of Native and Non-Native Cypriniformes Fish - Tamara Leite; Daniel Mameri; Paulo Branco; Inês Vieira; Margarida Oliveira; José Maria Santos (Fishes, 2023)
River ecosystems are exposed to a multitude of stressors, including increasing pesticide run-off driven by precipitation and irrigation. Pyrethroids are the fourth major group of insecticides in use worldwide and have extremely negative effects on aquatic fauna. In this study, we aimed to assess the effects of an acute 2 h sub-lethal exposure to different levels of the pyrethroid esfenvalerate on the swimming behaviour of two Cypriniformes species: the native Iberian barbel (Luciobarbus bocagei) and the non-native invasive bleak (Alburnus alburnus). The experimental set-up consisted of previous exposure to three esfenvalerate concentrations (control, 1.2 (low), and 2.0 (high) μg/L) before being stocked in a three-artificial-flume-channel mesocosm for behavioural trials through direct observation. Monitored behaviours included (i) routine activity, (ii) shoal cohesion, and iii) boldness. Significant differences in fish behaviour were detected for the native species (barbel), as individuals spent significantly more time holding position (i.e., resting) in the control (44.9%) than in the high esfenvalerate concentration (25.2%). Concordantly, control barbels were also found to perform more directional changes than the ones exposed to high esfenvalerate concentrations. Behavioural changes were also found for boldness, measured by the proportion of fish attempts to negotiate the upstream ramp, which were significantly higher in the control (37.4%) and in the high concentration (41.5%) compared to the low one (21.1%). Finally, regarding shoal cohesion of the barbel, it was tighter in the control (81.3%) than in the low- (70.5%) and high- (71.1%) esfenvalerate treatments. For the invasive bleak, there were no significant differences in any of the behavioural traits upon previous exposure to an increasing esfenvalerate concentration. This experimental study demonstrated that even short-term exposure to the pyrethroid esfenvalerate was sufficient to alter the behaviour of a native Cypriniformes fish species while not affecting the non-native species. This may confer greater competitive advantages to non-native fish species in the context of global changes.

β-Estradiol and progesterone enhance biofilm development and persister cell formation in monospecies and microcosms biofilms derived from vulvovaginal candidiasis - Ana Raquel Colares de Andrade; Mônica Dantas Sampaio Rezende; Fernando Victor Monteiro Portela; Livia Maria Galdino Pereira; Bruno Nascimento da Silva; Reginaldo Gonçalves de Lima-Neto; Marcos Fábio Gadelha Rocha; José Júlio Costa Sidrim; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2023)

Abundance and diversity of deep-sea crustaceans (Decapoda and Isopoda) in the upper slope of state of Pernambuco–Brazil: With five new records - Rômulo Costa Pires Ferreira; Danielle de Lima Viana; Paulo Guilherme Vasconcelos de Oliveira; Pollyana Christine Gomes Roque; Ilka Siqueira Lima Branco-Nunes; Alessandra Maria Advincula Pires; Diogo Martins Nunes; Fábio Hissa Vieira Hazin (Regional Studies in Marine Science, 2023)

Synergism between chikungunya virus infection and rheumatoid arthritis on cytokine levels: Clinical implications? - Luan Araújo Bezerra; Yan Charles da Silva Bastos; Juliana Prado Gonçales; José Valter Joaquim Silva Júnior; Virgínia Maria Barros de Lorena; Angela Luzia Branco Pinto Duarte; Claudia Diniz Lopes Marques; Maria Rosângela Cunha Duarte Coêlho (Brazilian Journal of Microbiology, 2023)

Four diterpenes identified in silico were isolated from Hyptidinae and demonstrated in vitro activity against Mycobacterium tuberculosis - Andreza Barbosa Silva Cavalcanti; Mayara dos Santos Maia; Pedro Thiago Ramalho de Figueiredo; Renata Priscila Barros de Menezes; Alex France Messias Monteiro; Roseana Araújo Ramos Meireles; Gabriela Cristina Soares Rodrigues; Ana Rita Rodrigues de Almeida Silva; Jociano da Silva Lins; Laísa Vilar Cordeiro; Valnês S. Rodrigues Junior; Ana Paula O. T. Castelo Branco; et al. (Natural Product Research, 2023)

Malassezia spp. and Candida spp. from patients with psoriasis exhibit reduced susceptibility to antifungals - Rossana de Aguiar Cordeiro; Ane Teles Reis; Xinaida Taligare Vasconcelos Lima; Ana Raquel Colares de Andrade; Ana Luiza Ribeiro Aguiar; Fernando Victor Monteiro Portela; Lívia Maria Galdino Pereira; Santiago Gonçalves Bezerra Moura; Bruno Nascimento da Silva; Reginaldo Gonçalves de Lima-Neto; Débora Castelo-Branco Souza Collare Maia; Marcos Fábio Gadelha Rocha; et al. (Brazilian Journal of Microbiology, 2023)

Promethazine inhibits efflux, enhances antifungal susceptibility and disrupts biofilm structure and functioning in Trichosporon - Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Nicole de Mello Fiallos; Lívia Maria Galdino Pereira; Maria Laína Silva; Pedro Freitas Santos Manzi de Souza; Fernando Victor Monteiro Portela; José Júlio Costa Sidrim; Marcos Fábio Gadelha Rocha; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2023)

Taubaracna maculosa: First fossil spider from paleogene in South America - Ariel Milani Martine; Marisa Vianna Mesquita; Ighor Carvalho; Beatriz Beloto; Fresia Ricardi-Branco; Maria Judite Garcia (Journal of South American Earth Sciences, 2023)

Immunological imbalance in microcephalic children with congenital Zika virus syndrome - Amanda Costa Ayres Salmeron; Wallace Pitanga Bezerra; Rafaela Lúcia Lopes de Souza; Luanderson Cardoso Pereira; Lícia Maria do Nascimento; Anna Cláudia Calvielli Castelo Branco; Luiza Emilia Cavalcanti Simas; Valéria Azevedo de Almeida; Pedro Henrique de Souza Palmeira; Christiane Medeiros Bezerra; Paulo Marcos Matta Guedes; Maria Notomi Sato; et al. (Medical Microbiology and Immunology, 2022)

Ecstasy metabolites and monoamine neurotransmitters upshift the Na+/K+ ATPase activity in mouse brain synaptosomes - Daniel José Barbosa; João Paulo Capela; Luísa Maria Ferreira; Paula Sério Branco; Eduarda Fernandes; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2022)

Efficiency tests for screening production strategies in a lettuce-juvenile tilapia aquaponics system in Brazil - Roberto Manolio Valladão Flores; Paul V. Preckel; Kwamena Quagrainie; Nicole Olynk Widmar; Laura Silva; Jesaias Ismael da Costa; Sara M. Pinho; Maria Célia Portella; Thais Castelo Branco; Manoel Xavier Pedroza Filho (Aquaculture International, 2022)

Heterologous extracellular DNA facilitates the development of Trichosporon asahii and T. inkin biofilms and enhances their tolerance to antifungals - Lívia Maria Galdino Pereira; Ana Raquel Colares de Andrade; Fernando Victor Monteiro Portela; Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Santiago Gonçalves Bezerra Moura; Mariana Lara Mendes Pergentino; Marcos Fábio Gadelha Rocha; José Júlio da Costa Sidrim; Débora de Souza Collares Maia Castelo Branco; Rossana de Aguiar Cordeiro (Biofouling, 2022)

Simultaneous changes in visual acuity, cortical population receptive field size, visual field map size, and retinal thickness in healthy human aging - Maria Fatima Silva; Ben M. Harvey; Lília Jorge; Nádia Canário; Fátima Machado; Mário Soares; Otília C. d’Almeida; Miguel Castelo-Branco (Brain Structure and Function, 2021)
Healthy human aging is associated with a deterioration of visual acuity, retinal thinning, visual field map shrinkage and increasing population receptive field sizes. Here we ask how these changes are related to each other in a cross-sectional sample of fifty healthy adults aged 20–80 years. We hypothesized that age-related loss of macular retinal ganglion cells may lead to decreased visual field map sizes, and both may lead to increased pRF sizes in the cortical central visual field representation. We measured our participants’ perceptual corrected visual acuity using standard ophthalmological letter charts. We then measured their early visual field map (V1, V2 and V3) functional population receptive field (pRF) sizes and structural surface areas using fMRI, and their retinal structure using high-definition optical coherence tomography. With increasing age visual acuity decreased, pRF sizes increased, visual field maps surface areas (but not whole-brain surface areas) decreased, and retinal thickness decreased. Among these measures, only functional pRF sizes predicted perceptual visual acuity, and Bayesian statistics support a null relationship between visual acuity and cortical or retinal structure. However, pRF sizes were in turn predicted by cortical structure only (visual field map surface areas), which were only predicted by retinal structure (thickness). These results suggest that simultaneous disruptions of neural structure and function throughout the early visual system may underlie the deterioration of perceptual visual acuity in healthy aging.

Distribution and migration phenology of Purple Martins (Progne subis) in Brazil - Clarissa O. Santos; Jonathan M. Branco; Maria C. T. D. Belotti; Pedro Abilleira; Joe Siegrist; Jason Fischer; Luciano M. Lima; Mario Cohn-Haft; Erika Hingst-Zaher (Ornithology Research, 2021)

Anthraquinones from Aloe spp. inhibit Cryptococcus neoformans sensu stricto : effects against growing and mature biofilms - Débora de Souza Collares Maia Castelo-Branco; Géssica dos Santos Araújo; Xhaulla Maria Quariguasi Cunha Fonseca; Glaucia Morgana de Melo Guedes; Maria Gleiciane da Rocha; Raimunda Sâmia Nogueira Brilhante; Rossana de Aguiar Cordeiro; José Júlio Costa Sidrim; Waldemiro Aquino Pereira-Neto; Marcos Fábio Gadelha Rocha (Biofouling, 2021)

Effects of intrinsic and extrinsic factors on the prevalence of the fungus Batrachochytrium dendrobatidis (Chytridiomycota) in stream tadpoles in the Atlantic Forest domain - Dener das Neves-da-Silva; Vitor Nelson Texeira Borges-Júnior; Christina Wyss Castelo Branco; Ana Maria Paulino Telles de Carvalho-e-Silva (Aquatic Ecology, 2021)

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Obesity as a risk factor for COVID-19: an overview - Ricardo Wesley Alberca; Luana de Mendonça Oliveira; Anna Cláudia Calvielli Castelo Branco; Nátalli Zanete Pereira; Maria Notomi Sato (Critical Reviews in Food Science and Nutrition, 2021)

Identification of flavonoids in Hymenaea martiana Hayne (Fabaceae) by HPLC-DAD-MS n analysis - Alessandra Gomes Marques Pacheco; Alexsandro Branco; Celso Amorim Câmara; Tânia Maria Sarmento Silva; Telma Maria Guedes Silva; Ana Paula de Oliveira; Alan Diego da Conceição Santos; Lívia Macedo Dutra; Larissa Araújo Rolim; Gibson Gomes de Oliveira; Jacqueline Nakau Mendonça; Norberto Peporine Lopes; et al. (Natural Product Research, 2021)

Opportunities and challenges of Eucalyptus plantations in Europe: the Iberian Peninsula experience - Margarida Tomé; Maria Helena Almeida; Susana Barreiro; Manuela R. Branco; Ernesto Deus; Glória Pinto; Joaquim S. Silva; Paula Soares; Roque Rodríguez-Soalleiro (European Journal of Forest Research, 2021)

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Feeding Ecology of Sicydium bustamantei (Greeff 1884, Gobiidae) Post-Larvae: The “Little Fish” of São Tomé Island - Vânia Baptista; Ester Dias; Joana Cruz; Maria Branco; Sara Vieira; Maria Alexandra Teodósio (Oceans, 2020)
The rivers of São Tomé Island are colonized by Sicydium bustamantei (Greeff 1882), an amphidromous fish that spawns in those areas. After hatching, larvae drift to the ocean with the river flow. In the marine realm, the planktonic larvae develop and migrate to freshwater as post-larvae. The migrations of post-larvae support important local fisheries at the mouth of rivers in tropical volcanic islands. Amphidromous post-larvae rely on plankton as their main source of organic matter. However, the biology and ecology of S. bustamantei in the West African islands are understudied, despite its importance for local fisheries. Thus, this study aimed to start bridging this gap by studying its feeding ecology. Our objectives were to identify the main prey of S. bustamantei post-larvae, combining gut content with stable isotope analyses. The gut contents included zooplankton (Chaetognatha, Ostracoda, and unidentified crustaceans), debris from plant and/or macroalgae-derived material, and microplastics (including microfibers). The stable isotopes analysis indicated that zooplankton and macroalgae detritus were the main sources of organic matter assimilated by this species. We also demonstrated that S. bustamantei post-larvae are omnivorous and secondary consumers. These data provide pioneering information that can be used in management plans that still need to be developed.

First ecotoxicological characterization of paraffin microparticles: a biomarker approach in a marine suspension-feeder, Mytilus sp - Bruno Nunes; Maria Inês Simões; Juan Carlos Navarro; Bruno Branco Castro (Environmental Science and Pollution Research, 2020)

Coenzyme Q10 Cardioprotective Effects Against Doxorubicin-Induced Cardiotoxicity in Wistar Rat - Ana Flávia M. Botelho; Marthin R. Lempek; Stephanie Elise M. T. Branco; Marina M. Nogueira; Maria Elvira de Almeida; Aristóteles G. Costa; Thalita G. Freitas; Michele Caroline R. C. Rocha; Matheus V. L. Moreira; Tatiane O. Barreto; Jader C. Santos; Gleidice Lavalle; et al. (Cardiovascular Toxicology, 2020)

Proposal for a microcosm biofilm model for the study of vulvovaginal candidiasis - Rossana de Aguiar Cordeiro; Ana Raquel Colares de Andrade; Fernando Victor Monteiro Portela; Lívia Maria Galdino Pereira; Santiago Gonçalves Bezerra Moura; Mônica Dantas Sampaio; Estefania Mota Araripe Pereira; Gláucia Morgana de Melo Guedes; Silviane Praciano Bandeira; Reginaldo Gonçalves de Lima-Neto; Vânia Maria Maciel Melo; Raimunda Sâmia Nogueira Brilhante; et al. (Biofouling, 2020)

Saponin-rich fraction from Agave sisalana : effect against malignant astrocytic cells and its chemical characterisation by ESI-MS/MS - João Victor A. de Oliveira; Mariana B. Botura; Jener D. G. dos Santos; Deivison S. Argolo; Victor Diogenes A. da Silva; Gisele D. da Silva; Hélimar G. de Lima; Raimundo Braz Filho; Ivo Jose C. Vieira; Alexsandro Branco; Maria José M. Batatinha; Silvia L. Costa (Natural Product Research, 2019)

Air quality monitoring assessment during the 2016 Olympic Games in Rio de Janeiro, Brazil - Luciana Maria Baptista Ventura; Michelle Branco Ramos; Adriana Gioda; Bruno Bôscaro França; Jose Marcus de Oliveira Godoy (Environmental Monitoring and Assessment, 2019)

Increase of Candida antarctica lipase B production under PGK promoter in Pichia pastoris: effect of multicopies - Julia Macedo Robert; Maritza Ocampo Betancur; Antonio Carlos Oliveira Machado; Andrelisse Arruda; Viviane Castelo Branco Reis; Rodrigo Volcan Almeida; Fernando Araripe Gonçalves Torres; Pau Ferrer Alegre; Francisco Valero; Denise Maria Guimarães Freire (Brazilian Journal of Microbiology, 2019)

Antifungal effects of the flavonoids kaempferol and quercetin: a possible alternative for the control of fungal biofilms - Marcos Fábio Gadelha Rocha; Jamille Alencar Sales; Maria Gleiciane da Rocha; Livia Maria Galdino; Lara de Aguiar; Waldemiro de Aquino Pereira-Neto; Rossana de Aguiar Cordeiro; Débora de Souza Collares Maia Castelo-Branco; José Júlio Costa Sidrim; Raimunda Sâmia Nogueira Brilhante (Biofouling, 2019)

The phenotypic relationship between residual intake and gain and other feed efficiency traits in Nellore cattle - Darcilene Maria de Figueiredo; Maria Eugênia Zerlotti Mercadante; Aldrin Vieira Pires; Renata Helena Branco; Enilson Geraldo Ribeiro; Gabriel Machado Dallago; Marianne Schorer; Pedro Ribeiro Rocha (Tropical Animal Health and Production, 2019)

Electrophysiological and behavioural responses of the Eucalyptus weevil, Gonipterus platensis, to host plant volatiles - Sofia Branco; Eduardo P. Mateus; Marco D. R. Gomes da Silva; Davide Mendes; Sílvia Rocha; Zvi Mendel; Stefan Schütz; Maria Rosa Paiva (Journal of Pest Science, 2019)

The Genus Alexandrium (Dinophyceae, Dinophyta) in Brazilian Coastal Waters - Mariângela Menezes; Suema Branco; Maria Cecília Miotto; Catharina Alves-de-Souza (Frontiers in Marine Science, 2018)

Cyanobacterial diversity held in microbial biological resource centers as a biotechnological asset: the case study of the newly established LEGE culture collection - Vitor Ramos; João Morais; Raquel Castelo-Branco; Ângela Pinheiro; Joana Martins; Ana Regueiras; Ana L. Pereira; Viviana R. Lopes; Bárbara Frazão; Dina Gomes; Cristiana Moreira; Maria Sofia Costa; et al. (Journal of Applied Phycology, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Sperm vitrification of Litopenaeus vannamei: effect of cryoprotectant solutions on sperm viability and spawning quality after artificial insemination - Thaís Castelo-Branco; Maria Madalena Pessoa Guerra; Roberta Soares; Silvio Peixoto (Aquaculture International, 2018)

Inhibitory effect of a lipopeptide biosurfactant produced by Bacillus subtilis on planktonic and sessile cells of Trichosporon spp. - Rossana de Aguiar Cordeiro; Ewerton Weslley Caracas Cedro; Ana Raquel Colares Andrade; Rosana Serpa; Antonio José de Jesus Evangelista; Jonathas Sales de Oliveira; Vandbergue Santos Pereira; Lucas Pereira Alencar; Patrícia Bruna Leite Mendes; Bárbara Cibelle Soares Farias; Vânia Maria Maciel Melo; Zoilo Pires de Camargo; et al. (Biofouling, 2018)

Digestion and metabolism of low and high residual feed intake Nellore bulls - Sarah Figueiredo Martins Bonilha; Renata Helena Branco; Maria Eugênia Zerlotti Mercadante; Joslaine Noely dos Santos Gonçalves Cyrillo; Fábio Morato Monteiro; Enilson Geraldo Ribeiro (Tropical Animal Health and Production, 2017)

Involvement of monoaminergic systems in anxiolytic and antidepressive activities of the standardized extract of Cocos nucifera L. - Eliane Brito Cortez Lima; Caren Nádia Soares de Sousa; Lucas Nascimento Meneses; Yuri Freitas e Silva Pereira; Natália Castelo Branco Matos; Rayanne Brito de Freitas; Nycole Brito Cortez Lima; Manoel Cláudio Azevedo Patrocínio; Luzia Kalyne Almeida Moreira Leal; Glauce Socorro Barros Viana; Silvânia Maria Mendes Vasconcelos (Journal of Natural Medicines, 2017)

Cytokines in Machado Joseph Disease/Spinocerebellar Ataxia 3 - Gerson da Silva Carvalho; Jonas Alex Morales Saute; Clarissa Branco Haas; Vitor Rocco Torrez; Andressa Wigner Brochier; Gabriele Nunes Souza; Gabriel Vasata Furtado; Tailise Gheno; Aline Russo; Thais Lampert Monte; Artur Schumacher-Schuh; Rui D’Avila; et al. (The Cerebellum, 2016)

Antidepressant, antioxidant and neurotrophic properties of the standardized extract of Cocos nucifera husk fiber in mice - Eliane Brito Cortez Lima; Caren Nádia Soares de Sousa; Germana Silva Vasconcelos; Lucas Nascimento Meneses; Yuri Freitas e Silva Pereira; Naiara Coelho Ximenes; Manuel Alves Santos Júnior; Natália Castelo Branco Matos; Rayanne Brito; Diogo Miron; Luzia Kalyne Almeida Moreira Leal; Danielle Macêdo; et al. (Journal of Natural Medicines, 2016)

Half Century Monitoring Air Pollution in a Megacity: a Case Study of Rio de Janeiro - Adriana Gioda; Luciana Maria Baptista Ventura; Michelle Branco Ramos; Mariana Palagano Ramalho Silva (Water, Air, & Soil Pollution, 2016)

A constitutive expression system for Pichia pastoris based on the PGK1 promoter - Andrelisse Arruda; Viviane Castelo Branco Reis; Vinícius Daniel Ferreira Batista; Bruno Sahim Daher; Luiza Cesca Piva; Janice Lisboa De Marco; Lidia Maria Pepe de Moraes; Fernando Araripe Gonçalves Torres (Biotechnology Letters, 2016)

Factors shaping contemporary patterns of genetic diversity of the Portuguese endemic cyprinids - Sousa Santos Carla; Robalo Joana; Pereira Ana; Branco Paulo; Santos José; Ferreira Maria; Sousa Monica; Doadrio Ignacio (Frontiers in Marine Science, 2016)

Feed efficiency, blood parameters, and ingestive behavior of young Nellore males and females - Sarah Figueiredo Martins Bonilha; Joslaine Noely dos Santos Gonçalves Cyrillo; Guilherme Pinheiro dos Santos; Renata Helena Branco; Enilson Geraldo Ribeiro; Maria Eugênia Zerlotti Mercadante (Tropical Animal Health and Production, 2015)

Approaches to preserve human osteochondral allografts - Eduardo Branco de Sousa; Diego Pinheiro Aguiar; José Fernando Marques Barcelos; Maria Eugênia Leite Duarte; Beni Olej (Cell and Tissue Banking, 2015)

Historical changes in the functional connectivity of rivers based on spatial network analysis and the past occurrences of diadromous species in Portugal - Pedro Segurado; Paulo Branco; Ana P. Avelar; Maria T. Ferreira (Aquatic Sciences, 2015)

Methane emission by Nellore cattle subjected to different nutritional plans - Olinta Leone Cota; Darcilene Maria de Figueiredo; Renata Helena Branco; Elaine Magnani; Cleisy Ferreira do Nascimento; Luiza Freitas de Oliveira; Maria Eugênia Zerlotti Mercadante (Tropical Animal Health and Production, 2014)

Simvastatin inhibits cytokines in a dose response in patients with rheumatoid arthritis - Michelly Cristiny Pereira; Pablo Ramon Gualberto Cardoso; Laurindo Ferreira Da Rocha; Moacyr Jesus Barreto Melo Rêgo; Sayonara Maria Calado Gonçalves; Flaviana Alves Santos; Marina Rocha Galdino-Pitta; Andréa Tavares Dantas; Ângela Luzia Branco Pinto Duarte; Maira Galdino Da Rocha Pitta (Inflammation Research, 2014)

"Ecstasy"-induced toxicity in SH-SY5Y differentiated cells: role of hyperthermia and metabolites - Daniel José Barbosa; João Paulo Capela; Renata Silva; Luísa Maria Ferreira; Paula Sério Branco; Eduarda Fernandes; Maria Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2014)

The mixture of “ecstasy” and its metabolites is toxic to human SH-SY5Y differentiated cells at in vivo relevant concentrations - Daniel José Barbosa; João Paulo Capela; Renata Silva; Vânia Vilas-Boas; Luísa Maria Ferreira; Paula Sério Branco; Eduarda Fernandes; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2014)

Effect of flow regime hydraulics on passage performance of Iberian chub (Squalius pyrenaicus) (Günther, 1868) in an experimental pool-and-weir fishway - Paulo Branco; José Maria Santos; Christos Katopodis; António Pinheiro; Maria Teresa Ferreira (Hydrobiologia, 2013)

Using Factor Analysis to Characterise Historical Trends of Trace Metal Contamination in a Sediment Core from the Tagus Prodelta, Portugal - Mário Mil-Homens; Vasco Branco; Cristina Lopes; Carlos Vale; Fátima Abrantes; Wim Boer; Maria Vicente (Water, Air, & Soil Pollution, 2009)

Role of the locus coeruleus carbon monoxide pathway in endotoxin fever in rats - Maria Ida Bonini Ravanelli; Maria C. Almeida; Luiz G. S. Branco (Pflügers Archiv - European Journal of Physiology, 2006)

New role of the trigeminal nerve as a neuronal pathway signaling brain in acute periodontitis: participation of local prostaglandins - Valeria P. Navarro; Mamie M. Iyomasa; Christie R. A. Leite-Panissi; Maria C. Almeida; Luiz G. S. Branco (Pflügers Archiv - European Journal of Physiology, 2006)

Candiduria in Hospital Patients: A Study Prospective - Cláudia Castelo Branco Artiaga Kobayashi; Orionalda de Fátima Lisboa Fernandes; Karla Carvalho Miranda; Efigênia Dantas de Sousa; Maria do Rosário Rodrigues Silva (Mycopathologia, 2004)

Role of the haem oxygenase-carbon monoxide pathway in insulin-induced hypothermia: evidence for carbon monoxide involvement - Maria Almeida; Luiz Branco (Pflügers Archiv - European Journal of Physiology, 2002)